(untitled) (Research, Society and Development, 2020)
The nutrients present in a diet can affect the the medication effects. Likewise, the drug can interfere with the absorption of some nutrients or even the effect of another drug. The objective was to evaluate the possible drug/drug interactions and between drugs/nutrients in geriatric and pediatric inpatients. Descriptive and transversal study developed in the geriatric and pediatric sectors of a Teaching Hospital in Pernambuco, Pernambuco, Brazil. Data collection took place between March and May 2018. Data was collected by consulting medical records of 20 elderly (≥60 years old) and 20 children (<12 years old) to identify possible drug/drug and drug/nutrient interactions . In the elderly cohort, the predominant gender was male (55%), the average age was 75.05±10.17 years and the most frequent disease was hypertension (45%). 145 types of potential drug/drug interactions and 147 possible drug/nutrient interactions were identified. In the cohort of children, the predominant gender was male (52.4%), aged between 3 months and 11 years and the most frequent disease was Sydenham’s Korea. 17 types of probable drug/drug interactions and 105 possible drug/nutrient interactions were identified. The findings indicate that there is a high risk of possible drug/drug and drug/nutrient interactions, both for assisted elderly (95%) and for hospitalized children (85%).